2021
DOI: 10.3390/toxins13020120
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Botulinum Neurotoxins in Dermatology: Systematic Review

Abstract: Botulinum toxin is a superfamily of neurotoxins produced by the bacterium Clostridium Botulinum with well-established efficacy and safety profile in focal idiopathic hyperhidrosis. Recently, botulinum toxins have also been used in many other skin diseases, in off label regimen. The objective of this manuscript is to review and analyze the main therapeutic applications of botulinum toxins in skin diseases. A systematic review of the published data was conducted, following Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 181 publications
0
33
0
5
Order By: Relevance
“…The strong efficacy and safety profile of BoNT-A1 for hyperhidrotic conditions has driven clinicians to evaluate its therapeutic potentiality in many other cutaneous diseases (Guida et al 2018 ). Scar prevention, as well as vascular and inflammatory skin disorders, oily skin, alopecia, rhytides and cutaneous lesions, are some of the novel indications for BoNT in cosmetic and notably non-cosmetic aspects of dermatology (Martina et al 2021 ; Naik 2021 ). These emerging clinical applications stem also from recent evidence that the BoNT/A1 receptors and intracellular targets are not unique for neurotransmission.…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong efficacy and safety profile of BoNT-A1 for hyperhidrotic conditions has driven clinicians to evaluate its therapeutic potentiality in many other cutaneous diseases (Guida et al 2018 ). Scar prevention, as well as vascular and inflammatory skin disorders, oily skin, alopecia, rhytides and cutaneous lesions, are some of the novel indications for BoNT in cosmetic and notably non-cosmetic aspects of dermatology (Martina et al 2021 ; Naik 2021 ). These emerging clinical applications stem also from recent evidence that the BoNT/A1 receptors and intracellular targets are not unique for neurotransmission.…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%
“…More recent retrospective reviews have suggested the role of the intradermal injection of BoNT-A1 in decreasing sebum production and pore size with high patient satisfaction without significant side effects (Shuo et al 2019 ). Intradermal BoNT-A1 injection may represent an innovative promising treatment for oily skin and other relevant dermatological problems, such as enlarged pores, acne, and seborrheic dermatitis (Martina et al 2021 ).…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the authors conducted an in vitro study, suggesting inhibiting TGF-B1 secretion from the hair follicles by the intradermal injection of botulinum toxin may be the potential action mechanism of BoNT-A in treating AGA. Despite the promising results of the mentioned research, recently published systemic reviews underline that there is still a need to conduct randomized, placebo-controlled studies in this area [ 55 , 56 , 57 ].…”
Section: Role Of Bont In Dermatologymentioning
confidence: 99%
“… 52 Due to its unique versatility, BTX is also being used in many other dermatologic conditions, in off label regimen. 53 In a recent pilot animal study, is has been used experimentally to investigate its effect on hair follicle cell regeneration under continuous stress conditions. The authors concluded that BTX may be a positive indicator for hair loss treatment but future studies are warranted.…”
Section: Mesotherapymentioning
confidence: 99%